Lo nacional y lo utópico como recursos identitarios - Gustafsson, Jan E. C. (Diálogos Latinoamericanos, 2008)
The so-called ’left turn’ that have taken place in Latin American politics since 1999, seems to correspond to a profound revision of neo-liberal economics and politics of the 1980’s and 90’s. Part of this revision seems to be a revitalization of the nation state as an economic, political and symbolic (identity) resource. Another important aspect of the increasing influence of the left is the ‘return of utopia’. This utopia is not identical to the socialist and left utopias of the 60’s and 70’s, as part of the new and radical left in Latin America tends to see nation and utopia as two sides of a coin. This fact calls the attention to the case of Cuba, often thought of as an obsolete ‘left-over’ of past decades, as the Cuban ‘model’ actually combines two discourses: the utopian and the national. The article presents shortly a theoretical frame-work and discusses some general elements of national(ist) and utopian identity discourse. Finally it discusses some basic elements of the Cuban model.